A typical presentation of infective endocarditis - Loong, Yik Yee; A., Fadzli; Lim, P. H.; G., Rakhi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
We describe a patient who had fever and bilateral cortical blindness and was later found to have leaking intracerebral mycotic aneurysm secondary to Staphylococcus aureus endocarditis. He had vegetation at the tricuspid valve with evidence of systematic embolization; however, chest radiograph did not reveal any evidence of pulmonary emboli.